TRACING INFILTRATION AND RECHARGE USING STABLE ISOTOPE IN TAIHANG MT., NORTH CHINA - Li F.; Song X.; Tang Ch.; Liu Ch.; Yu J.; Zhang W. (My University, 2007)
The groundwater in headwater region is an important recharge source for the adjacent mountain-front plain. In order to reveal the relationship among precipitation, soil water and groundwater, from June to September in 2004, stable isotopes (deuterium and oxygen-18) in precipitation and soil waters at the depths of 10, 20, 30, 50, 70, 90, and 110 cm were analyzed at two sites covered by black locust (Robinia Pseudoacia L.) (Site A) and grass predominated by Themeda triandra (T. japonica (Willd.) Tanaka) and Bothriochloa ischaemum (B. ischaemum (L.) Keng) (Site B) in an experimental catchment at Taihang Mt., North China, respectively. The δ18O of precipitation in daily rain events shows large variations (−13.3 to −4.3‰) with a mean of 8.1‰. The δ18O and δ D of soil waters along profiles in two sites suggest that the influence of canopy cover was just up to 10 cm in top soil water. The soil water moved over the zero flux plane at 70 cm in-depth is expected to escape the evaporative effect at the end of September in both sites. The results show that the stable isotope, instead of tritium as tradition, can be used to trace the soil water behaviors based on the movement of isotopic peak along the vertical profiles in this semi-arid and semi-humid mountainous region. The infiltration depths of soil water in Taihang Mt. are 12 and 10 mm/day from June to September in 2004 in Site A and Site B, respectively. Tracing by stable isotope, recharge fluxes of soil water to local groundwater are of 3.8 and 3.2 mm/day in Site A and Site B, respectively. The results provide desirable information for assessment of local groundwater resources.
Keywords: STABLE ISOTOPES; PRECIPITATION; SOIL WATER; GROUNDWATER; INFILTRATION; RECHARGE; TAIHANG MT.